Pengaruh Strategi Resource-Based dan Orientasi Kewirausahaan terhadap Keunggulan Bersaing Usaha Kecil dan Usaha Mikro (Studi pada Usaha Jasa Etnis Maluku) - Metekohy, Stellamaris (Jurnal Aplikasi Manajemen, 2013)
Important role small and medium industry in economics of Indonesia uncompatible with competitiveness storey; level, publication of The Global of Competitiveness Report published by World Economic Forum in the year 2008 showing Indonesia competitiveness storey; level in global emulation reside in sequence of ke-55 from 134 state. This research have the character of exsplanatory with quantitative approach, Population [is] the overall of small effort/ethnical micro effort Moluccas which have activity to service sector, while sampel which used in this research 100 responder. Sampling technique in this research use sampling method of nonprobabilitas, by using technique of judgment sampling. strategy of Resource based which aqualitation and resource of kapabilitas have an effect on to improve orientation of kewirausahaan. strategy of resource better based can improve competitiveness in the case of excellence of expense, excellence of small industry diferensiasi and ethnical micro effort of Moluccas specially the effort service. Orient kewirausahaan in the case of attitude of inovatif, risking proaktif can improve small industry competitiveness and ethnical micro effort Moluccas in the case excellence of expense, excellence of diferensiasi and excellence of focus.